(untitled) (Technological Innovations Journal, 2022)
The objective of the research was to determine the effectiveness of the use of virtual learning environments in solving algebraic problems in first grade secondary school students. The approach used was quantitative, experimental and quasi-experimental design. The study sample consisted of two groups of equivalent students, one control and one non-randomized experimental group with pre and posttest. The instruments used were four tests, one on the ability to translate data and conditions into algebraic expressions, another on the ability of students to communicate their understanding of algebraic relationships, another on the ability to use strategies and procedures to find general rules and the last, on the ability to argue statements about exchange and equivalence relationships, which were subjected to a validation and reliability process. The results show that the use of virtual learning environments in the students of the experimental group differs significantly in relation to the students of the control group, this is evidenced in the statistical test of the difference in means, where Zc is -3.14, which is less than the critical value -1.96, at a significance level of 5%. The research allowed us to conclude that the use of virtual learning environments as a teaching resource is effective in solving mathematical problems.